Social Jet Lag and Overweight in Youth - Pozo-García, María del Pilar (2026)
Sleep is a vital function for human beings; therefore, adequate sleep is essential for the healthy development of people. It is conceived as a neurobehavioral state that occupies between 20 and 40% of the day, influenced by biological, behavioral, environmental and personal/social factors. Sleep quality includes aspects such as satisfaction, duration, regularity, and ability to stay alert; however, factors such as age, chronotype, light, noise, mood, and certain lifestyle habits can negatively affect sleep. Circadian rhythms, regulated by a central clock in the hypothalamus, synchronize bodily functions with the light and dark cycle. Discrepancies between biological clocks and social schedules (social jet lag) due to work or study led to sleep insufficiency and "chronodisruption". In youth, this is associated with poor sleep quality, irregular eating, and increased risk of obesity and mood disorders. Therefore, it is important to promote regular sleep habits to mitigate these negative effects and improve the overall health of young people.